IMPLEMENTASI EVALUASI MODEL KIRKPATRICK PADA PROGRAM PELATIHAN PENGGUNAAN EYD V SMK BROADCASTING MAHARDIKA - Ryan Hidayat; Bambang Perkasa Alam; Ukti Lutvaidah; Prima Pantau Putri Santosa (Abdi Jurnal Publikasi, 2023)
In the digital era like today, the use of good and correct Indonesian is becoming increasingly important. To improve students' ability to use the Indonesian language, Broadcasting Mahardika Vocational School held a training program on the use of EYD V. However, a training program must be evaluated in order to find out how effective the program is in achieving the stated goals. Therefore, the Kirkpatrick evaluation model was used to evaluate the effectiveness of the EYD V training program at SMK Broadcasting Mahardika. The Kirkpatrick evaluation model is used because it is one of the most widely known and used training evaluation models. Kirkpatrick's evaluation model consists of four levels, namely: Level 1: Reaction, Level 2: Learning, Level 3: Behavior, and Level 4: Results. Through the application of the Kirkpatrick evaluation model, the training program for using EYD V at SMK Broadcasting Mahardika will be evaluated from these four aspects so that it can be seen how effective the training program is in increasing students' ability to use Indonesian properly and correctly. In the evaluation results using the Kirkpatrick model, it is hoped that the weaknesses and strengths of the training program will be found, and can provide recommendations to increase the effectiveness of the training program in the future. The application of good and correct Indonesian is increasingly important in today's digital era. Through the training program on the use of EYD V held by SMK Broadcasting Mahardika, it is hoped that it can improve students' ability to use the Indonesian language properly and correctly. The Kirkpatrick evaluation model is used to evaluate the effectiveness of the EYD V training program at Broadcasting Mahardika Vocational School, so that the weaknesses and strengths of the training program can be found and provide recommendations for increasing effectiveness in the future.